Coastal Cities and Environmental Change. (1st November 2014) - Mosley, Stephen
Abstract : This paper explores the complex environmental relationships of coastal cities with their shorelines and the sea. Cities developed in coastal locations because they offered easy access to fisheries, trade and commerce, transport, attractive scenery and recreational opportunities. However, coastal cities have also been vulnerable to the natural hazards of hurricane-force winds, tsunamis and tidal flooding; and climate change will exacerbate flood risks in the future. Many of the world's largest cities are situated by the sea, and today in every continent except North America the highest share of urban dwellers live in coastal zones. These issues, together with growing concerns over the state of the world's oceans - declining fish stocks, aquatic ecosystem degradation, and marine acidification - have attracted growing historical interest in coastal cities and their role in environmental change. Using examples of different types of coastal cities, I survey how growing urbanisation, trade, industrialisation and tourism impacted on shorelines and the sea over time. I also examine how communities have adapted to the challenges and risks of living in coastal cities. The paper concludes by offering some suggestions for further inquiry.